The Influence of Performance-Contingent Rewards on Proactive and Responsive Creativity: Dual-Path Mediating Effects of Work Motivation - Li, Chunling; Jiang, Xinqing; He, Hui; Zhang, Xiying (Frontiers in Psychology, 2022)
Creativity has become prevalent in the routine work of knowledge employees in contemporary enterprises. From the perspective of ambidexterity, drawing upon expectancy theory and self-determination theory (SDT), the present study highlights the driver behind proactive and responsive creativity. Using two-stage longitudinal data collected from 373 knowledge employee-supervisor dyads in information and manufacturing companies in China, the results show that: (1) performance-contingent rewards have an inverted U-shaped influence on proactive creativity and a U-shaped influence on responsive creativity; (2) performance-contingent rewards have an inverted U-shaped influence on autonomous and controlled motivation; (3) autonomous motivation has a positive influence on proactive creativity, but controlled motivation has a negative influence on responsive creativity; (4) autonomous and controlled motivation play a partly mediating mechanism in the non-linear effects of performance-contingent rewards on proactive and responsive creativity, respectively. Managers should enhance the ambidextrous ability to deal with proactive and responsive creativity and establish an applied and dynamic policy of performance-contingent rewards intensity to drive ambidextrous creativity.